Competition and Innovation in Automobile Markets - Vivek Ghosal; Jiayao Ni (Center for Economic Studies and ifo Institute (CESifo), 2015)
Using data from the U.S. automobile market, we empirically examine the link between competition and innovation. Consistent with a large literature, we use patent counts as a measure of innovation. The combination of the U.S. market's economic importance, market dynamics, and the significant intertemporal fluctuations in firms' market shares and patents make this an interesting market to examine the link between competition and innovation. We use firm-level time-series data over a long horizon (1969-2012) for nine well established firms selling in the U.S. market (GM, Ford, Chrysler, Toyota, Honda, Nissan, Volkswagen, BMW, and Daimler). Some of our key findings are: (1) increase in firms' market shares result in higher patenting, and the relationship is reasonably non-linear; (2) higher market-wide competition results in an increase in patenting, and the relationship is weakly non-linear; (3) the (absolute) quantitative impact on patents is larger for firms' market share effect as compared to market-wide competition; (4) there is relatively strong path-dependence in firms' patenting behavior; and (5) we find interesting results linking patents to GM's bankruptcy, the Daimler-Chrysler merger, environmental regulations, voluntary export restraints, and firms' patenting over business cycles.
Keywords: L13; L62; O31; D21; M21; 330; patents; innovation; market share; competition; automobiles; business cycles; mergers; environmental regulations; antitrust